2022
DOI: 10.1136/bmjopen-2021-053865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine and meperidine for the prevention of shivering following coronary artery bypass graft: study protocol of a randomised controlled trial

Abstract: IntroductionShivering is a common complication in the postoperative period. The incidence of shivering has been reported to range from 5% to 65% under general anaesthesia and as 33% during epidural anaesthesia. Shivering can increase perioperative risk in patients. Both dexmedetomidine and meperidine are effective agents for the prevention of postanaesthetic shivering. However, few studies have compared the anti-shivering effects of different agents following coronary artery bypass graft (CABG). This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…The current study showed that both Dexmedetomidine 0.5 µg/kg and Tramadol 0.5mg/kg decreased the incidence and intensity of shivering in patients exposed to elective operations under spinal anaesthesia when compared to the control group, but these drugs could not prevent the significant decrease in the core temperature after the subarachnoid block. This anti-shivering effect was not associated with increased side effects 8 .…”
Section: Discussionmentioning
confidence: 70%
“…The current study showed that both Dexmedetomidine 0.5 µg/kg and Tramadol 0.5mg/kg decreased the incidence and intensity of shivering in patients exposed to elective operations under spinal anaesthesia when compared to the control group, but these drugs could not prevent the significant decrease in the core temperature after the subarachnoid block. This anti-shivering effect was not associated with increased side effects 8 .…”
Section: Discussionmentioning
confidence: 70%
“…Se ha reportado una incidencia del temblor postoperatorio, que oscila entre el 5% y el 65% bajo anestesia general y el 33% bajo anestesia neuroaxial 4 . La hipotermia perioperatoria es la principal causa de temblor postoperatorio debido a la inhibición del mecanismo termorregulador 7 .…”
Section: Discussionunclassified
“…El temblor postoperatorio es un movimiento involuntario que afecta a una o varias fibras musculares, generalmente se presenta en la primera fase de la recuperación tras anestesia general 3 . De acuerdo a datos establecidos la incidencia fluctúa entre 6 y 66%; predomina en género masculino y se ha visto que el tiempo y tipo de cirugía parecen ser uno de los factores determinantes para su presentación 4 .…”
Section: Introductionunclassified
“…In addition, its metabolites can cause central nervous system symptoms of excitement. 4,9,10 Butorphanol is a mixed agonist and antagonist of the opioid receptor. It produces analgesic and shivering resistance effects for moderate affinity to the κ opioid receptor (KOR), with partial antagonism to the μ opioid receptor (MOR), so it has little effect on respiration and circulation with minor adverse reactions.…”
Section: Introductionmentioning
confidence: 99%